Reporting Confidence Decreases Response and Change-of-Mind Accuracy in a Perceptual Decision Task. - Litwin, Piotr; Paulewicz, Borysław; Siedlecka, Marta (Journal of Experimental Psychology. Human Perception & Performance, 2025)
Self-monitoring seems to be crucial for regulatory behavior, but it is not clear how it influences performance in simple cognitive tasks. Some studies suggest that increased monitoring improves metacognitive regulation and enhances performance, while others suggest it impairs learning, problem solving, or perceptual processes. We investigated whether the requirement to report confidence in perceptual decisions affects metacognitive regulation and response accuracy. Participants performed a visual discrimination task in which they provided two responses: initial and final. Depending on the condition, participants reported their confidence (either together with or following the initial decision), performed an additional task, or were asked to observe a blank screen between two responses. We expected that reporting decision confidence would induce efficient regulatory activity, which would benefit final accuracy. In three experiments, we did not find evidence that rating confidence improves regulatory processing or performance in perceptual tasks. Rather, when confidence ratings were retrospective, the final response improvement was smaller compared to the condition with no additional task, and changes of mind were less frequent and less corrective. Confidence ratings given jointly with the initial response generally decreased accuracy. The results suggest that deliberate monitoring might put additional strain on cognitive resources and impair lower-order task processing. Public Significance Statement: In this study, participants made perceptual decisions but were given a chance to change their initial responses. The results showed, contrary to our predictions, that assessing confidence in an initial response might lead to less accurate response changes and smaller improvement in task accuracy than in the control condition, in which there were no confidence assessments. The findings suggest that deliberate confidence monitoring is a cognitively demanding task that might hinder any potential use of confidence as a cue about decision accuracy or difficulty.